The epidemiology of injuries in professional sitting volleyball athletes - Mahmoudkhani, M.; Alizadeh, F.; Khodsiyani, E.; Norouzi, M. (The Physician and Sportsmedicine, 2025)
Objectives This study investigated the epidemiology of injury among players at the Iran Sitting Volleyball Super League 2023-2024.